Chronology and documentary handbook of the State of Delaware - Frech, Mary L. (Dobbs Ferry, N.Y. : Oceana Publications, 1973)
Contains a chronology of historical events from 1742 to 1977, a biographical directory of prominent citizens, and selected documents including the State constitution of 1889.
Cover title: Montana, a chronology & documentary handbook.
Includes index.
Bibliography: p. 147-148.
Keywords: Montana -- History -- Chronology; Montana -- Biography; Montana -- History -- Sources; Montana -- History